2023
DOI: 10.1186/s12903-023-02881-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the accuracy of automated cephalometric analysis based on artificial intelligence

Abstract: Background The purpose of this study was to evaluate the accuracy of automatic cephalometric landmark localization and measurements using cephalometric analysis via artificial intelligence (AI) compared with computer-assisted manual analysis. Methods Reconstructed lateral cephalograms (RLCs) from cone-beam computed tomography (CBCT) in 85 patients were selected. Computer-assisted manual analysis (Dolphin Imaging 11.9) and AI automatic analysis (Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Similar results were achieved by other research teams, demonstrating a superior AI success classification rate compared to humans in some cephalometric analysis measures [30,31,45]. An interesting study by Bao et al (2023) evaluated the accuracy of AI in the automated cephalometric analysis of reconstructed lateral cephalograms from CBCTs for 85 patients. The mean radial error for 19 chosen landmarks was 2.07 ± 1.35 mm and an error of less than 3 mm in 71.7% with the automatic program.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar results were achieved by other research teams, demonstrating a superior AI success classification rate compared to humans in some cephalometric analysis measures [30,31,45]. An interesting study by Bao et al (2023) evaluated the accuracy of AI in the automated cephalometric analysis of reconstructed lateral cephalograms from CBCTs for 85 patients. The mean radial error for 19 chosen landmarks was 2.07 ± 1.35 mm and an error of less than 3 mm in 71.7% with the automatic program.…”
Section: Discussionsupporting
confidence: 67%
“…The mean radial error for 19 chosen landmarks was 2.07 ± 1.35 mm and an error of less than 3 mm in 71.7% with the automatic program. The authors concluded that automatic analysis is almost effective enough to be acceptable in clinical work, but is not currently capable of completely replacing manual tracing [46]. Some minor inaccuracies have also been found in previously published papers regarding the reliability of CephX cephalometric analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, since the reference points are used in a further step of the cephalometric analysis to perform angular measurements [ 52 ], a potential limitation of the proposed framework is that such measurements and index data were not obtained. Nevertheless, it should be noted that the cephalometric angles depend to a large extent on the correct positioning of the reference points.…”
Section: Discussionmentioning
confidence: 99%
“…In general, acceptable linear and angular measurement are less than 2 mm and 2 • , respectively [23,36,38,43,44,47,54,[66][67][68][69][70]. Following this criterion, although some commercially available software can achieve high overall accuracy in automated landmarking on lateral cephalograms, manual supervision is still recommended [47,48,53,54,56].…”
Section: Cephalometric Analysismentioning
confidence: 99%